Slavonic-greek-latin Academy in Moscow and its reforms from the 2d quarter of the XVIIIth c. up to the beginning of the XIXth c. in the context of evolution of the high education in Russia - Larionov Aleksei (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article’s purpose is the analysis of the evolution process and all its main aspects in the history of Moscow Slavonic-greek-latin Academy of the speciﬁed period. At the beginning of the XVIII century Moscow Academy was found on a basis of European «pre-classical» university pattern and became the ﬁrst higher institute for all social estates in Russia. After the Peter’s the Great death the Academy experiences reduction of material security and contraction of the students’ social estate. Another tendency is also observed - the penetration of European university modernization ideas in Russia provokes the start of several national university projects. During the Catherine’s the Second reign these ideas inﬂuence on the evolution of the Academy as well as already generated Academy educational tradition inﬂuences the speciﬁed university projects. This reciprocal eﬀect leads the creation of separate higher educational systems: secular, under the Ministry of National Enlightenment, and theological, under the Holy Synod. The sources allow tracking the participation of higher state and church ﬁ gures working together on both structures. As a result Moscow Academy served as a sample for other theological academies and thus has become the foundation of the whole theological education system